1995
DOI: 10.1093/clinids/20.3.588
|View full text |Cite
|
Sign up to set email alerts
|

Dental Infection and the Risk of New Coronary Events: Prospective Study of Patients with Documented Coronary Artery Disease

Abstract: Several recent studies have suggested that dental infections are associated with coronary artery disease. To further elucidate this association, we conducted a prospective 7-year follow-up study of 214 individuals (182 males and 32 females; mean age, 49 years) with proven coronary artery disease who had undergone a dental examination and evaluation for the classic coronary risk factors at entry. The main outcome measures were the incidence of fatal and nonfatal coronary events and overall mortality. Fifty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
197
3
22

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(230 citation statements)
references
References 25 publications
8
197
3
22
Order By: Relevance
“…In addition, we compared the explanatory ability of the ADS to that of the TDI, formulated by Mattila et al 15 To observe clinically meaningful robust changes, we created an ordinal scale of ADS under the assumption that an increased score would be associated with an increased risk of CHD. To make a fair comparison, we also created a TDI scale with the same assumption.…”
Section: Validationmentioning
confidence: 99%
“…In addition, we compared the explanatory ability of the ADS to that of the TDI, formulated by Mattila et al 15 To observe clinically meaningful robust changes, we created an ordinal scale of ADS under the assumption that an increased score would be associated with an increased risk of CHD. To make a fair comparison, we also created a TDI scale with the same assumption.…”
Section: Validationmentioning
confidence: 99%
“…2 Moreover, an association has been shown to exist among chronic infections, inflammatory markers, and CHD. [2][3][4] The concept that chronic infection plays a role in the pathogenesis of CHD may have important clinical implications. Current research on the infective hypothesis of CHD has focused mainly on Chlamydia pneumoniae and Helicobacter pylori.…”
mentioning
confidence: 99%
“…In a 7-year CHD and also for further coronary events. The study by Beck et al 23 confirmed the findings of these investigators, 24 indicating that periodontal disease may be a risk factor for CHD. Beck et al 23 reported that subjects with the most severe probing depths and bone loss at baseline had higher risk for developing CHD than those with minimal periodontal disease.…”
Section: Discussionmentioning
confidence: 58%